2018
DOI: 10.1080/02640414.2018.1532152
|View full text |Cite
|
Sign up to set email alerts
|

Fatness and fitness in relation to functional movement quality in overweight and obese children

Abstract: This study aimed to investigate the independent and combined associations between several fatness indicators and fitness components with functional movement quality in overweight/obese children. A total of 56 children (33 girls, aged 8-12) classified as overweight/obese according to the World Obesity Federation standard cut points, participated in this study. Participants underwent assessments of fatness [body mass index (BMI), waist circumference, and bioelectrical impedance measures], fitness [1 repetition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 45 publications
3
55
2
Order By: Relevance
“…On the other hand, speed agility was associated with shorter RT in both loads, indicating faster information processing speed regardless of the working memory demands. A recent study using the same sample as in the present research found that higher speed agility was associated with better movement competency . Proper movement competency is partly determined by a neuromuscular/motor control network, which may also relate to shorter RTs.…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, speed agility was associated with shorter RT in both loads, indicating faster information processing speed regardless of the working memory demands. A recent study using the same sample as in the present research found that higher speed agility was associated with better movement competency . Proper movement competency is partly determined by a neuromuscular/motor control network, which may also relate to shorter RTs.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have reported considerably larger inverse associations between BMI and FMS scores then in the current study (r ranged from -0.3 to -0.81) [19,20,34,40,41]. Notably, several studies have reported that the strength of the association between BMI and motor coordination declines as children start to reach puberty [62,63], which might explain some of the above-mentioned disparity in findings between the current and previous research.…”
Section: Discussioncontrasting
confidence: 81%
“…Therefore, investigating relations between adiposity and FM is important for the musculoskeletal health of the mid-adolescents as well. Only a handful of studies have focused on studying movement quality and obesity in the paediatric population with the majority reporting an inverse relationship between FM and weight status [19,20,34,40,41], while only one study revealed no correlation between these two variables [42]. However, these studies have been performed on a small number of conveniently selected children, or recruited only participants with overweight/obesity, and did not include mid-adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…(Fisher-Wellman & Bloomer, 2010). In this way, exercise-training will cause a decrease in lipids in the adipocytes, reducing fat mass concomitant to an improvement in the child's body composition (Molina-Garcia et al, 2019;K. S. Steinbeck, 2001).…”
Section: Overall Pathways Of Exercise To Treat Obesitymentioning
confidence: 99%
“…The practice of regular exercise is seen as a fundamental instrument in the process of the prevention and treatment of obesity (Mogul, Irby, & Skelton, 2014), and childhood obesity (McCambridge et al, 2006;McManus & Mellecker, 2012), since it is associated with greater recruitment of muscle mass along with an increased local hyperemia, inducing improvement in lipid profile, glucose uptake and blood pressure control (Molina-Garcia et al, 2019;Monteiro et al, 2015;Mortensen & Saltin, 2014;Noland, 2015). A meta-analysis demonstrated that exercise is associated with a significant increase in adiponectin and maintenance of leptin and resistin levels (García-Hermoso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%